New Publications in Forensic Science - N. V. Fetisenkova; A. A. Ignat’eva (Теория и практика судебной экспертизы)
This section presents translated abstracts of selected papers that appeared in the following periodicals: Forensic Science International, volumes 278–279 (2017) and volume 254 (2015), Elsevier Ireland Ltd. (Netherlands) [journal homepage: www.elsevier.com/locate/forsciint], and Journal of Forensic Sciences, volume 63, number 3 (2018), Wiley (USA) [available online at: www. onlinelibrary.wiley.com].